Synchronous Acute Appendicitis, Perforated Cecal Diverticulitis and Serrated Adenoma of Right-Sided Colon: An Uncommon Incidental Finding - Metin Yalaza; Mehmet Tolga Kafadar; Ahmet Türkan; Gürkan Geğirmencioğlu; Özgür Akgül (Southern Clinics of Istanbul Eurasia, 2017)
Right iliac fossa pain is one of the most common reasons for a patient visit to the emergency department. Although appendicitis is the most common condition requiring surgery in patients with abdominal pain, right iliac fossa pain can be indicative of a vast list of differential diagnoses, and is thus both a diagnostic and a therapeutic challenge for clinicians. In this article, an exceedingly rare case of right iliac fossa pain in a 54-year-old male who had not just solitary perforated cecal diverticulitis, but also acute appendicitis and serrated adenoma of the ascending colon is presented. The final diagnosis was made by postoperative histopathological examination. To the best of our knowledge, this is the first reported case with these 3 different entities simultaneously present in the same patient.